The meaning of work of Makassar Tribe Farmers: A case study in Batulapisii, Malino Suburb, Gowa Regency, South Sulawesi, Indonesia. Issue 3 (July 2021) - Busthanul, N; Demmallino, E B; Ali, S S; Nadja, R A; Syafiuddin, M; Djalaluddin, A; Amrullah, A; Noor, A A
Abstract: Every ethnic Makassar farmer has a meaning that is relevant to the values of the Makassar Tribe in the form of instrument, social, intellectual and expressive meanings in carrying out farming activities, both subsistence farmers who are oriented towards moral choices, meaning that they carry out farming activities only to meet basic and commercial needs. farmer oriented. Rational choice means running farming activities to get maximum benefits. This study aims to describe the rice farming activities in the Batulapisii environment, to describe the meaning of the work of rice farmers in the Batulapisi environment, and to identify the Makassar values that are relevant to the meaning of the work of farmers. This study uses a qualitative descriptive approach. The results showed that the farming that developed in the Batulapisii environment, namely rice and horticulture, as well as subsistence farmers and commercial farmers, had four existing meaning criteria, namely the meaning of the instrument, the social meaning, the intellectual meaning and the meaning of the expression, with some Makassar values relevant to the meaning of farmer work.